Pendampingan Distribusi Bantuan Peralatan Kerja Bengkel Z-Auto Program pada Baznas Provinsi Jawa Timur (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
The welfare of the community in the economic sector is one of the benchmarks for the welfare of the community, there are many people who experience poverty which is motivated by economic factors, the national amil zakat agency offers the jatim Makmur program. a program that really needs manpower considering that there are several workshop equipment that must be distributed to mustahik to do business. The method of assistance in the activities carried out by the national amil zakat agency of East Java province is an annual program activity, namely the Makmur program, which is carried out from July 14-16. One of the programs of the national amil zakat agency of East Java province, namely the Makmur program, is a program that moves in the economic field, which has two objectives, namely the development and empowerment of the economy in the community, the Makmur program distributes work equipment assistance z auto, some of the work equipment assistance distributed is among others such as Grobak workshops, workshop tools, other than that the amil zakat agency not only provides assistance in the form of z auto repair shop equipment but along with the basic materials needed by the workshopsuchas stock oil, andso on, the distribution of work equipment assistance Z auto Makmur jatim program has a positive value for the community, namely providing benefits regarding the empowerment and development of mustahik so that z auto repair shop business actors are able to become muzakki and donate a little of their wealth to people in need, assistance in the distribution of the jatim Makmur program is in accordance with the category of 8 asnaf at least with the category of poor or underprivileged people.